PELAKSANAAN KEBIJAKAN STANDARISASI TANGGUNG JAWAB SOSIAL WARUNG INTERNET (WARNET) DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Fitri, Rahma Wahyuli; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Information and communication technology is growing rapidly at the moment of iron and the internet has become a necessity to get information now , previous and forthcoming .. many problems arise because the lack of social responsibility of business owners of internet cafes , which affects both children internet misuse children , adolescents, and , dewasa.Oleh is why local governments have delegated authority to the relevant parties in the implementation of the standardization problem of internet cafes (cafe ) in Kota Pekanbaru this study aims to identify and recognize , and the factors that influence the implementation of standardization policy social responsibility of internet cafes (cafe ) in Kota Pekanbaru Rumbai Pesisir subdistrict .Researchers used the theory of Van Meter and Van Horn who said that the successful implementation of a policy is influenced by the standards and policy objectives, resources, implementing organizational characteristics, komunisi among organizations, attitudes and environmental policy implementation is the social, economic, and political. This study uses a triangulation technique is an activity check, re-check and crosscheck.The results of this study indicate that factors that influence the implementation of the standardization policy of social responsibility in the city of Pekanbaru District of Coastal Rumbai not been implemented to the maximum. Implementation of the standards reasonably good internet cafes, the social responsibility of implementing internet cafes has not done well, the resources needed inadequate, lack of information and communication, is the refusal of the executive standardization interenet shop, economic and less political support.Keywords: Standardization Policy